2017
DOI: 10.1002/anie.201701627
|View full text |Cite
|
Sign up to set email alerts
|

Robust Binding between Carbon Nitride Nanosheets and a Binuclear Ruthenium(II) Complex Enabling Durable, Selective CO2 Reduction under Visible Light in Aqueous Solution

Abstract: Carbon nitride nanosheets (NS-C N ) were found to undergo robust binding with a binuclear ruthenium(II) complex (RuRu') even in basic aqueous solution. A hybrid material consisting of NS-C N (further modified with nanoparticulate Ag) and RuRu' promoted the photocatalytic reduction of CO to formate in aqueous media, in conjunction with high selectivity (approximately 98 %) and a good turnover number (>2000 with respect to the loaded Ru complex). These represent the highest values yet reported for a powder-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
166
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(172 citation statements)
references
References 52 publications
1
166
0
Order By: Relevance
“…It is well-known that the organic semiconductor g-C 3 N 4 possesses visible light harvesting properties due to its narrow band gap energy (≈2.7 eV) [15]. Thus g-C 3 N 4 has emerged as a promising polymeric semiconductor for photocatalytic reduction of carbon dioxide (CO 2 ) [1620], hydrogen evolution [2125], oxidation of NO [2627], and degradation of pollutants [2830]. However, the photocatalytic performance of bulk g-C 3 N 4 remains unsatisfactory because of the fast recombination rate of electron pairs and narrower light absorption range over the entire solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the organic semiconductor g-C 3 N 4 possesses visible light harvesting properties due to its narrow band gap energy (≈2.7 eV) [15]. Thus g-C 3 N 4 has emerged as a promising polymeric semiconductor for photocatalytic reduction of carbon dioxide (CO 2 ) [1620], hydrogen evolution [2125], oxidation of NO [2627], and degradation of pollutants [2830]. However, the photocatalytic performance of bulk g-C 3 N 4 remains unsatisfactory because of the fast recombination rate of electron pairs and narrower light absorption range over the entire solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The ruthenium complex (X = PO 3 H 2 ) held the best performance of converting CO 2 into HCOOH with TON >1000 and QY reaching 5.7% at 400 nm. Later, the same group built a PCN‐based Z‐scheme system with the Ru(II) binuclear complex comprising of both photosensitizing and catalytic units, possessing high selectivity for CO 2 reduction toward HCOOH (87−99%) and producing a TON of ≈33 000 for 48 h with a nanoparticulate Ag modifier . This study indicated that the bifunctional binuclear metal molecular complexes could be much more efficient than the mononuclear metal complexes in photocatalysis.…”
Section: Photocatalytic Application With Metal/pcn Systemsmentioning
confidence: 98%
“…In order to improve the optical properties of TiO 2 , it has been combined with various metals to form hybridized composites such as Ag/TiO 2 15 , Pt/TiO 2 16 , Ru/TiO 2 17 , Pd/TiO 2 18 , Ni/TiO 2 19 , Cu/TiO 2 20 , TiO 2 /Cu-TiO 2 21 , CeO 2 -TiO 2 22 , MgO-TiO 2 23 , NiO-In 2 O 3 /TiO 2 24 , CuS x -TiO 2 25 , NiS-TiO 2 26 , In 2 O 3 /TiO 2 27 , TiO 2 /Fe-TiO 2 28 and multi-walled carbon nanotube (MWCNT)@TiO 2 29 in an attempt to reduce the band gap or suppress recombination of photogenerated charge carriers. Also, catalysts having a combination of an organic and metal material such as g-C 3 N 4 30 , Ni 12 P 5 /g-C 3 N 4 31 , Au cluster-NP/C 3 N 4 32 , AgX/g-C 3 N 4 (X = Cl and Br) 33 , RuRu′/Ag/NS-C 3 N 4 3437 and Co-ZIF 3841 are being developed.…”
Section: Introductionmentioning
confidence: 99%